Pengaruh Penganggaran Terhadap Penyaluran Bantuan Dana Desa Pada Masyarakat Desa Cikubang Tasikmalaya - Cepi Juniar Prayoga (JPA : Journal of Public Accounting, 2021)
This study aims to determine the effect of budgeting on the distribution of cikubang village funds. he method used in this research is quantitative method and the data used is secondary data. The sample used in this study is village financial statements that meet the specified criteria. The sampling technique used was purposive sampling method. The data analysis used in this research is Simple Regression Analysis. The results of this study indicate that budgeting has a significant effect on the distribution of village funds. This means that if the budget increases, the distribution of village funds will also increase.